Trans-splenic anterograde coil assisted transvenous occlusion (TACATO) of gastric varices associated with gastrorenal shunt. (March 2023) - Shalaby, S.; Battistel, M.; Miraglia, R.; Angeli, P.; Feltracco, P.; Burra, P.; Zanetto, A.; Barbiero, G.; Senzolo, M.
Abstract : Background: The management of gastric varices (GV) depends on anatomical and hemodynamic features and balloon-occluded retrograde transvenous obliteration (BRTO) is recommended for the occlusion of GV-associated with gastro-renal shunts (GRS). We report a prospective case-series in which we used the trans-splenic route to perform occlusion of GV for prophylaxis of variceal bleeding or refractory encephalopathy. Methods: Trans-splenic access was obtained by puncturing a splenic venous branch under ultrasound/fluoroscopic guidance. Through a 5-Fr sheath a 2.7"microcatheter was introduced into the varices and embolization was performed using detachable microcoils +/- a mixture of N-butyl-cyanoacrylate (NCBA)-Lipiodol. A venography was performed to assess technical success. The percutaneous tract was embolized using a NBCA-Lipiodol mixture. All patients underwent upper gastrointestinal-endoscopy at follow up to evaluate worsening of esophageal varices and amelioration of GV. Results: Ten patients with different indications were enrolled: 3 for primary prophylaxis (1 GOV1, 2 IGV1), 6 for secondary prophylaxis (1 GOV1, 5 GOV2) of GV bleeding and 1 for post-transplant shunt-related persistent encephalopathy (IGV1). In all patients, the GRS [median size 22mm (range 15-32mm)]was accessed by trans-splenic route and the GV was embolized with a median of 10 microcoils (range 5-18), with addition of NBCA-Lipiodol in 6patients. The mean time in the angiography suite was 135min (range 105-180min), while the mean procedure-time was 75min (range 45-120min). Besides mild local abdominal pain at access, 3 patients presented acute partial splenic +/- portal thrombosis, which regressed in all with anticoagulation. During follow-up (median 5months, range 1-12months) no bleeding was observed, liver function remained stable and no patient developed/worsened ascites. Endoscopic follow-up showed a significant reduction of GV or filling with coils (Fig.1), without worsening of esophageal varices. Conclusions: TACATO seems to be a safe and efficient method to obliterate GV associated with GRS and it can be considered as alternative to BRTO in the algorithm of treatment.